Self-Directed Learning in the era of the COVID-19 pandemic Research on the affordances of online virtual excursions - Geldenhuys, Yolani (NWU Self-Directed Learning Series, 2022)
The COVID-19 pandemic severely impacted teaching and learning at higher education institutions (HEIs), and this book disseminates research findings on a series of cross-campus online initiatives of the North-West University (NWU) to ensure high-quality self-directed learning, whilst simultaneously attending to the need for inclusion and diversity in this challenging context. The golden thread running through the 13 chapters is how this HEI responded to the pandemic in a creative way through its investment in online virtual student excursions, based on problem-based, cooperative learning and gamification principles to support self-directed learning. Whereas virtual excursions usually refer to learning opportunities where 'a museum, author, park or monument is brought to the student' (Hehr 2014:1), the virtual excursion in our context is an activity system (Engeström 1987) where students' learning is scaffolded across the zone of proximal development (Vygotsky 1978) and where their 'social and pedagogical boundaries are stretched or expanded' (De Beer & Henning 2011:204). Students engage as Homo ludens, the playing human (Huizinga 1955), in learning activities embedded in an ill-structured problem, and through reflective activities, they are encouraged to reflect on their own naïve understandings or biases. This 'tension', or in Veresov (2007) parlance, 'dramatical collisions', provides a fertile learning space for self-directed learning.